Natural Durability of Nine Woods Species Grown in Dramaga Campus Bogor Agricultural University against Termite Attacked - fauzi Febrianto; Andi Z Pranata; Arinana Arinana; Adiyantara Gumilang (Masyarakat Peneliti Kayu Indonesia, 2013)
The objective of this research was to evaluate the natural durability of nine Indonesia lesser known species against subterranean termite (Coptotermes curvignathus Holmgren) and dry wood termite (Cryptotermes cynocephalus Light) attacked grown in Dramaga campus, Bogor Agricultural University. Sap and hearth wood parts of mangium, durian, nangka, angsana, afrika, rukam, trembesi, bisbul, and ki sampang woods with diameter around 13-30 cm were used in this experiment. Evaluation of natural durability of wood referred to SNI 01-7207-2006. The hearth wood of nangka wood was the most durable wood against C. curvignathus attacked and it was classified into 2nd class. Bisbul, rukam and trembesi woods both sap and herath wood and heart wood of angsana wood were classified into 3rd class. Mangium and afrika woods both sap and hearth woods were classified into 4th class. Ki sampang and durian woods both sap and hearth woods and sap wood of nangka and angsana woods were classified into 5th class. All the 9 woods species (i.e. rukam, bisbul, mangium, ki sampang, afrika, nangka, durian, angsana and trembesi woods) both sap and hearth wood parts were moderately resistance to C. cynocephalus and they were classified into 3rd class.Key words: dry wood termite, hearth wood, lesser known species, natural durability, sap wood, subterranean termite